Robotics and LOMLOE: Systematic revision of robotics as inclusive tool - Gómez Jiménez, Óscar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The present study carries out a systematic review of the scientific literature on robotics as a tool to promote school inclusion, based on what is explained in the LOMLOE. In the analysis, the filters of the PRISMA statement and the CASP checklist have been applied, selecting studies belonging to the SCOPUS, WOS, and Scholar Google databases. The main conclusions expose the improvement of social and communication skills and the enhancement of motivation and teamwork capacity thanks to the inclusion of robotics in the academic curriculum.